The Application of Safety Riding for Kids on the Attitudes and Behavior of Kindergarten Students In Indramayu Regency - Eko Maulana Syaputra; Tayong Siti Nurbaeti; Riantina Luxiarti; Sarinah Basri K; Irna Kartina (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
Data from the Indramayu Police Station in 2018 reported that there were 107,968 traffic accidents with the number of victims of 29,083 died. Victims of traffic accidents were 2,546 aged 0-4 years. The high number of traffic accidents occurs due to poor attitudes and behavior in the aspect of safe driving attitude. Many parents do not require their children to wear helmets or other safety gear when dropping off or picking up their children from school. Although children are extremely vulnerable to serious injuries if a traffic accident occurs. The aims of this study was to investigate the effect of implementing safety riding for kids on the attitudes and behavior towards safety riding behavior in kindergarten students. There were 36 students recruited in intervention group and 47 students in the control group. This study used a quasi-experimental type of research. Data were collected using a questionnaire. Pretest was done before giving treatment, postest data was taken after 3 months of treatment, data analysis of this research used Wilcoxon test.The results found that in the intervention group there were differences in attitudes and behaviors about safety riding before and after intervention with a p-value of 0,005 and 0,000, respectively. In the control group, there were no differences in attitudes and behaviors about safety riding with a p-value of 0,231 and 0,074, respectively. There is an effect of the implementation of safety riding for kids on the attitudes and behavior about safety riding with a p-value of 0,000. There is effect of the application of safety riding for kids on the attitudes and behavior of kindergarten students in Indramayu Regency.